The ancient central Andes - Quilter, Jeffrey 1949- (Routledge, 2014)
"The Ancient Central Andes presents a general overview of the prehistoric peoples and cultures of the Central Andes, the region now encompassing most of Peru and significant parts of Ecuador, Bolivia, northern Chile, and northwestern Argentina. The book contextualizes past and modern scholarship and provides a balanced view of current research. Two opening chapters present the intellectual, political, and practical background and history of research in the Central Andes and the spatial, temporal, and formal dimensions of the study of its past. Chapters then proceed in chronological order from remote antiquity to the Spanish Conquest.The book presents background on the history of research in the region as well as current investigations. Consensus opinions on interpretations are highlighted as are disputes among scholars regarding interpretations of the past. A number of important themes run through the book including the tension in between those scholars who wish to study Peruvian antiquity on a comparative basis in contrast to historicist approaches. The Ancient Central Andes provides an up-to-date, objective survey of the archaeology of the central Andes that is much needed. Students and interested readers will benefit greatly from this introduction to a key period in South America's past"--